Lethal salinity and survival for Macrobrachium carcinus larvae subjected to osmotic stress - Lima, João Paulo V.; Melo, Fabiana P.; Ferreira, Maria Gabriela P.; Flickinger, Dallas L. [UNESP]; Andrade, Humber A.; Correia, Eudes S. (My University, 2021)
The present study aimed to establish an adequate salinity range for the larviculture of the Macrobrachium carcinus by determining the lethal salinity (LS50) and survival of the larvae subjected to osmotic stress tests. Newly hatched larvae were acclimated at the salinities of 16 and 20 and reared for 20–22 days until reaching Zoea stage VI (ZVI). The larvae were then subjected to two osmotic stress tests carried out in 2-L plastic recipients (1–1.6L used volume) with a density of 50 larvae/L and with constant aeration. Each salinity had three replicates. Survival was recorded every 24 h after exposure to the salinities. In Test 1, ZVI larvae were transferred without acclimatization from salinity 16 to 0, 4, 8, 12, 16 (control), 20, 24 and 28 for 96 h. In Test 2, ZVI larvae were transferred without acclimatization from salinity 20 to 0, 4, 8, 12, 16, 20 (control), 24, 28, 32, 36 and 40 for 120 h. In both tests, 100% mortality of ZVI M. carcinus larvae was observed during the first hours upon altering the salinity to 0 and 4. Total mortality occurred at 72 h in the salinity of 40. In Test 1 (96 h), the best survival was shown with salinities between 16 and 24, with a maximum of 46.7% in 20 and 24. In Test 2 (120 h), the best survival was observed in salinities between 16 and 32, with a maximum of 71.3% in 28. The linear model generated from both tests (R2 = 92.8%) indicated that survival is optimized by using a salinity between 16 and 28. The LS50 (120 h) was estimated at 11.58 in the lower range and 33.70 in the upper range. In general, M. carcinus larvae in the Pre-culture phase (Zoea stages I to VI) of the larviculture showed more resistance to osmotic stress when reared in brackishwater with a salinity of 20 when compared with the salinity of 16, and the salinity range of 16–28 was the most adequate for the cultivation of ZVI M. carcinus larvae.
Keywords: Aquaculture; Conservation; Freshwater prawns; Larvae; Lethal salinity; Logistic model